2014
DOI: 10.1089/acm.2014.0220
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effectiveness of Bee Venom Acupuncture and Physiotherapy in the Treatment of Adhesive Capsulitis: A One-Year Follow-Up Analysis of a Previous Randomized Controlled Trial

Abstract: BVA combined with physiotherapy remains clinically effective 1 year after treatment and may help improve long-term quality of life in patients with AC of the shoulder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 18 publications
1
40
0
1
Order By: Relevance
“…In humans, however, it has been used as an anti-inflammatory medicine to relieve pain and treat chronic inflammatory diseases such as rheumatoid arthritis and multiple sclerosis [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. While bee venom itself causes nociceptive and neurotoxic effects, several recent studies have demonstrated that bee venom has radioprotective [ 8 ], antimutagenic [ 9 ], anti-inflammatory [ 7 , 10 , 11 , 12 , 13 , 14 ], anti-nociceptive [ 15 , 16 , 17 ] and anti-cancer [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ] activities.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, however, it has been used as an anti-inflammatory medicine to relieve pain and treat chronic inflammatory diseases such as rheumatoid arthritis and multiple sclerosis [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. While bee venom itself causes nociceptive and neurotoxic effects, several recent studies have demonstrated that bee venom has radioprotective [ 8 ], antimutagenic [ 9 ], anti-inflammatory [ 7 , 10 , 11 , 12 , 13 , 14 ], anti-nociceptive [ 15 , 16 , 17 ] and anti-cancer [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ] activities.…”
Section: Introductionmentioning
confidence: 99%
“…Its biological purpose is to protect the bees from their enemies. Because of its anti-inflammatory, anti-bacterial, antimutagenic, radioprotective, anti-nociceptive immunity-promoting, hepatocyte-protective and anti-cancer characteristics [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ], it has a long history of use in folk medicine to treat various diseases. Traditionally, live bees are used to sting acupuncture points for the affected area.…”
Section: Introductionmentioning
confidence: 99%
“…Bee venom acupuncture likewise has for a long time been a traditional approach in oriental medicine for the relief of pain and inflammation. In the treatment of shoulder stiffness, bee venom acupuncture in combination with physiotherapy was shown to be beneficial compared with placebo treatment and physiotherapy, especially in improving functioning capacity and relieving pain [44,45].…”
Section: Acupuncturementioning
confidence: 99%